Morocco : Request for an Arrangement Under the Precautionary and Liquidity Line and Cancellation of the Current Arrangement. (IMF Staff Country Reports; Country Report ;, 2014)
EXECUTIVE SUMMARY Morocco's economic track record was challenged in recent years by a series of exogenous shocks, to which the authorities responded vigorously. Facing a difficult international environment, the authorities adopted, with the support of the Fund's Precautionary and Liquidity Line (PLL), a policy program aimed at restoring fiscal and external buffers while strengthening competitiveness and promoting higher and more inclusive growth. The program remained broadly on track and the authorities did not draw on the PLL. The outlook is improving but remains subject to significant downside risks. Growth will slow in 2014, but it is expected to accelerate over the medium term owing to structural reforms and improved global conditions. However, this outlook remains subject to major external risks. A protracted period of slower growth in Europe, a surge in global financial market volatility linked to the exit from unconventional monetary policies in large advanced economies, and higher oil prices resulting from geopolitical tensions could significantly degrade the balance of payments. The authorities are requesting a two-year successor PLL arrangement with a lower access (550 percent of quota) than the first arrangement. The current PLL has provided useful insurance against external risks while anchoring the authorities' reform agenda and sending positive signals to markets. Given significant global risks, a successor arrangement, which the authorities intend to treat as precautionary, would continue to support their policies. The lower access reflects the strengthening of the economy in the past two years as well as a balance of risks lower than two years ago. Staff considers that Morocco continues to qualify for a PLL arrangement and recommends the approval of the authorities' request. The proposed arrangement carries low risks to the Fund and would have minimal impact on the Fund's liquidity were the authorities to draw on the full amount available. The authorities' policy package provides reasonable prospects of exit at the end of this arrangement if external circumstances warrant.